Truncated HBx‐dependent silencing of GAS2 promotes hepatocarcinogenesis through deregulation of cell cycle, senescence and p53‐mediated apoptosis. Issue 1 (28th May 2015) - Zhu, Ranxu; Mok, Myth TS; Kang, Wei; Lau, Suki SK; Yip, Wing‐Kit; Chen, Yangchao; Lai, Paul BS; Wong, Vincent WS; To, Ka‐Fai; Sung, Joseph JY; Cheng, Alfred SL; Chan, Henry LY
Abstract Hepatocellular carcinoma (HCC) is a worldwide threat to public health, especially in China, where chronic hepatitis B virus (HBV) infection is found in 80–90% of all HCCs. The HBV‐encoded X antigen (HBx) is a trans‐regulatory protein involved in virus‐induced hepatocarcinogenesis. Although the carboxyl‐terminus‐truncated HBx, rather than the full‐length counterpart, is frequently overexpressed in human HCCs, its functional mechanisms are not fully defined. We investigated the molecular function of a naturally occurring HBx variant which has 35 amino acids deleted at the C‐terminus (HBxΔ35). Genome‐wide scanning analysis and PCR validation identified growth arrest‐specific 2 (GAS2) as a direct target of HBxΔ35 at transcriptional level in human immortalized liver cells. HBxΔ35 was found to bind the promoter region of GAS2 and attenuate its expression to promote hepatocellular proliferation and tumourigenicity. Further functional assays demonstrated that GAS2 induces p53‐dependent apoptosis and senescence to counteract HBxΔ35‐mediated tumourigenesis. Notably, GAS2 expression was significantly down‐regulated in HCCs compared with the corresponding normal tissues. In conclusion, our integrated study uncovered a novel viral mechanism in hepatocarcinogenesis, wherein HBxΔ35 deregulates cell growth via direct silencing of GAS2 and thereby provides a survival advantage for pre‐neoplastic hepatocytes to facilitate cancer development. Copyright © 2015 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.